Acute restraint stress augments the rewarding memory of cocaine through activation of α1 adrenoceptors in the medial prefrontal cortex of mice. (April 2020) - Wada, Shintaro; Yanagida, Junko; Sasase, Hitoki; Zhang, Tong; Li, Xueting; Kamii, Hironori; Domoto, Masaki; Deyama, Satoshi; Hinoi, Eiichi; Yamanaka, Akihiro; Nishitani, Naoya; Nagayasu, Kazuki; et al.
Abstract: Stress augments the rewarding memory of cocaine, which plays a critical role in inducing cocaine craving. However, the neurobiological mechanisms underlying the enhancing effect of stress remain unclear. Here, we show that noradrenaline (NA) transmission in the medial prefrontal cortex (mPFC) mediates stress-induced enhancement of cocaine craving. When mice were exposed to acute restraint stress immediately before the posttest session of the cocaine-induced conditioned place preference (CPP) paradigm, the CPP score was significantly higher than that in non-stressed mice. Because extracellular NA levels have been reported to be increased in the mPFC during stress exposure, we assessed the effects of NA on mPFC layer 5 pyramidal cell activity. Whole-cell recordings revealed that NA application induces depolarization and a concomitant increase in spontaneous excitatory postsynaptic currents (sEPSCs). The NA effects were inhibited by terazosin, but not by yohimbine or timolol, and the sEPSC increase was not observed in the presence of tetrodotoxin, suggesting the involvement of postsynaptic α1, but not α2 or β, adrenoceptors in the NA effects. Additionally, intra-mPFC injection of terazosin before stress exposure attenuated the stress-induced increase in cocaine CPP. Intra-mPFC injection of phenylephrine, an α1 adrenoceptor agonist, before the posttest session without stress exposure significantly enhanced cocaine CPP. Furthermore, chemogenetic suppression of mPFC pyramidal cells with inhibitory DREADD (designer receptors exclusively activated by designer drugs) also suppressed the stress-induced CPP enhancement. These findings suggest that the stress-induced increase in NA transmission activates mPFC pyramidal cells via α1 adrenoceptor stimulation, leading to enhancement of cocaine craving-related behavior. Highlights: Acute restraint stress enhances cocaine CPP in mice. NA excites mPFC layer 5 pyramidal cells via α1 adrenoceptor stimulation. Blockade of mPFC α1 adrenoceptors reduces the stress-induced CPP enhancement. Chemogenetic inhibition of mPFC suppresses the stress-induced CPP enhancement.